Cunoniaceae infructescences from the early Eocene Laguna del Hunco flora, Patagonia, Argentina. Issue 6 (15th June 2022) - Matel, Theodore P.; Gandolfo, María A.; Hermsen, Elizabeth J.; Wilf, Peter
Abstract: Premise: Two distinct types of fossil infructescences from the early Eocene Laguna del Hunco flora, Chubut Province, Patagonia, Argentina, preserve features of the family Cunoniaceae. The goal of the study was to assess their affinities within Cunoniaceae and to interpret their evolutionary and biogeographical significance. Methods: Specimens were collected from the Tufolitas Laguna del Hunco, Huitrera Formation. They were prepared, photographed, and compared morphologically with similar extant and fossil fruits and infructescences using published literature and herbarium material. Results: The fruit and infructescence morphology place the fossil taxa within Cunoniaceae. They do not conform to any extant genus, supporting the erection of two new fossil genera. Racemofructus gen. nov. shares diagnostic features of the tribe Cunonieae, especially Weinmannia s.l., and exhibits two tribal morphological synapomorphies: a racemose inflorescence and a replum composed of a single column. Cunoniocarpa gen. nov. specimens are paniculate inflorescences with basipetally dehiscent, bicarpellate capsules that have persistent styles and calyces. Its replum morphology suggests an affinity to the tribe Caldcluvieae, particularly to the genus Ackama . Conclusions: The new Patagonian fossils described herein constitute the oldest record of cunoniaceous capsules globally, supplementing a significant body of fossil evidence from pollen, wood, and reproductive structures from southern South America and Antarctica that suggests that the Cunoniaceae were diversified and widely distributed in the southern hemisphere by the early Eocene. Racemofructus and Cunoniocarpa are, respectively, the first fossil records from South America of reproductive structures with affinity to tribes Cunonieae and Caldcluvieae.